TEACHING ITALIAN LANGUAGE THROUGH SONGS: A PROPOSAL FOR FOREIGN LEARNERS - Ferrante, Virgie Emilysal (Вестник ЗКУ, 2022)
The work presented was born as a teaching proposal for teaching a second language for foreign learners based on an approach defined in humanistic-affective language teaching. This involves the learner in his meaningful learning process, so as to favor a deep and lasting assimilation that takes into account the weight of the emotional component in the acquisition process with the aim of eliminating the components of stress and anxiety. It is believed that a learning proposal based on the use of the song in the classroom can be useful in order to involve the learner in his meaningful learning process. We want to propose a type of teaching that favors learning, but which, at the same time, is pleasant to follow in line with the passions and interests of the class group. This proposal focused on the use of the song to be systematically included in the weekly activities.